Age and Education Effects on a Novel Syntactic Assessment Battery for Elderly Adults - Sung, Jee Eun; Ahn, Heekyung; Choi, Sujin; Lee, Kiseop (Frontiers in Psychology, 2021)
The purpose of this study was to delineate the properties of a novel syntactic assessment battery and to present descriptive data on normal elderly individuals. We administered the Syntactic Assessment Battery (hereinafter SAB) using a sentence-picture paradigm to 195 normal elderly adults in three age groups (60–69, 70–79, 80–90) and five educational levels (No formal education, Elementary School Graduation, Middle School Graduation, High School Graduation, College Graduation and Above). A multiple linear regression model was applied to verify the age and education effects. A summary of results indicated that the SAB effectively detected age and education effects. People generally demonstrated worse performance as they aged but better performance as their educational levels increased. People with high school education and above generally demonstrated stronger performance on the test, although educational effects were not significantly different between elementary and middle school graduation groups. The current novel syntactic assessment battery can serve as a screening measure that sensitively detects age and education effects.